Effects of mild heat exposure on fatigue responses during two sets of repeated sprints matched for initial mechanical output - Soo, J.; Racinais, S.; Bishop, D. J.; Girard, O. (Journal of Science and Medicine in Sport, 2022)
Objectives: We examined whether mild heat exposure alters performance, perceptual responses and neural drive to the quadriceps during two sets of repeated sprints matched for initial mechanical output. Design: Repeated measures. Methods: Twelve males performed 10 6-s sprints (recovery=30s), followed 6min later by 5 6-s sprints (recovery=30s) in either COOL (24C/30% rH) or HOT (35C/40% rH) conditions. Subsequently, two sets of five consecutive sprints matched for initial mechanical output were compared. Results: On the basis of peak power, performance in sprint 2 was not significantly different to sprint 11 in both conditions (p<0.32). Average peak power across the five sprints compared (i.e.,sprints 2.6 and 11.15, respectively) was 2.6-?3.4% higher in HOT compared to COOL (p=0.025). Electromyographic activity (root mean square value) of the vastus lateralis-muscle remained unchanged. Core (sprints 2 6: 37.85+-0.21 vs.37.53 0.19C, sprints 11 15: 38.26 0.33 vs. 37.89? 0.24 C;p<?0.001) and skin (sprints 2 6: 36.21 0.29 vs. 30.72 0.52 C, sprints 11 15: 36.37 ?0.28 vs. 30.99 0.55 C; p<0.001) temperatures were overall higher in HOT compared to COOL. Heart rate, thermal sensation and comfort were significantly elevated in HOT compared to COOL (p<0.02), irrespective of sprint number. Conclusions: When two sets of repeated sprints were matched for initial mechanical output, performance was enhanced with mild heat exposure. This occurred despite higher thermal, cardiovascular, and perceptual strain, and without alterations in quadriceps neural drive. repeated sprints matched for initial mechanical output.